anonymous
  • anonymous
8+2/3(2n-9)=10
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
8+(2)/(3)*(2n-9)=10 Multiply each term by a factor of 1 that will equate all the denominators. In this case, all terms need a denominator of 3. 8*(3)/(3)+(2(2n-9))/(3)=10 Multiply the expression by a factor of 1 to create the least common denominator (LCD) of 3. (8*3)/(3)+(2(2n-9))/(3)=10 Multiply 8 by 3 to get 24. (24)/(3)+(2(2n-9))/(3)=10 The numerators of expressions that have equal denominators can be combined. In this case, ((24))/(3) and (2(2n-9))/(3) have the same denominator of 3, so the numerators can be combined. ((24)+2(2n-9))/(3)=10 Simplify the numerator of the expression. (4n+6)/(3)=10 Factor out the GCF of 2 from each term in the polynomial. (2(2n)+2(3))/(3)=10 Factor out the GCF of 2 from 4n+6. (2(2n+3))/(3)=10 Multiply each term in the equation by 3. (2(2n+3))/(3)*3=10*3 Simplify the left-hand side of the equation by canceling the common terms. 2(2n+3)=10*3 Multiply 10 by 3 to get 30. 2(2n+3)=30 Divide each term in the equation by 2. (2(2n+3))/(2)=(30)/(2) Simplify the left-hand side of the equation by canceling the common terms. 2n+3=(30)/(2) Simplify the right-hand side of the equation by simplifying each term. 2n+3=15 Since 3 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 3 from both sides. 2n=-3+15 Add 15 to -3 to get 12. 2n=12 Divide each term in the equation by 2. (2n)/(2)=(12)/(2) Simplify the left-hand side of the equation by canceling the common terms. n=(12)/(2) Simplify the right-hand side of the equation by simplifying each term. n=6
anonymous
  • anonymous
n=6
anonymous
  • anonymous
hopefuly helps you out

Looking for something else?

Not the answer you are looking for? Search for more explanations.